A Qualitative Study of Plantations for their Quantitative Ranking - Pandey, R. R. (Indian Forester, 1998)
To evaluate the plantations for rank. grade and status. quality criteria were selected. implementing Plantation Quality Index (PQI). using models. This methodology can be used with pre-decided parameters for plantations.